Magnetic multi-effect organic-inorganic composite amphiphilic particle as well as preparation method and application thereof

By using magnetic multi-performance organic and inorganic composite amphiphilic particles, which consist of core-shell-separated magnetic Fe3O4 particles and silica shell layer, it solves the problem that it is difficult to efficiently remove oil-containing wastewater containing partially hydrolyzed polyacrylamide in the prior art, realizes oil-water separation and efficient removal of organic wastewater in the sewage, and supports multiple uses, reducing treatment costs.

CN119701883AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202311262672.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove oil-containing wastewater containing partially hydrolyzed polyacrylamide while separating oil and water.

Method used

Magnetic multi-performance organic and inorganic composite amphiphilic particles are used, which consists of the core and shell separated magnetic Fe3O4 particles and the silica shell. The outer surface of the silica shell has hydrophilic and hydrophobic parts. The inner surface and the inner core surface of the magnetic Fe3O4 particles are grafted with polydiethylaminoethyl methacrylate (PDEAEMA), and the adsorption and migration of partially hydrolyzed polyacrylamide is achieved through the micro-porous structure.

Benefits of technology

It realizes efficient removal of partial hydrolyzed polyacrylamide while oil-water separation, and the particles can be reused multiple times, reducing the material cost of wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004473446850000191
    Figure BDA0004473446850000191
  • Figure BDA0004473446850000201
    Figure BDA0004473446850000201
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and provides a magnetic multi-effect organic-inorganic composite amphiphilic particle as well as a preparation method and application thereof. The magnetic multi-effect organic-inorganic composite amphiphilic particle comprises a core-shell separated magnetic Fe3O4 particle inner core and a silicon dioxide shell layer, the outer surface of the silicon dioxide shell layer comprises a hydrophilic part and a hydrophobic part, the hydrophilic part is used for modifying the outer surface of the silicon dioxide shell layer by an amino-containing silane coupling agent, so that the outer surface of the silicon dioxide shell layer is provided with amino, and the amino is grafted with polydopamine; the inner surface of the silicon dioxide shell layer and the surface of the magnetic Fe3O4 particle inner core are grafted with poly (diethylaminoethyl methacrylate), and the silicon dioxide shell layer has a fine hole structure. The magnetic multi-effect organic-inorganic composite amphiphilic particle provided by the invention has excellent emulsifying performance and can realize oil-water separation; and meanwhile, the adsorbent also has a selective adsorption characteristic, and can be used for efficiently treating oily sewage containing part of hydrolyzed polyacrylamide in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and more specifically to a magnetic multi-functional organic-inorganic composite amphiphilic particle and a preparation method and application thereof. Background Art

[0002] Oily wastewater from oilfields is often accompanied by high concentrations of partially hydrolyzed polyacrylamide (HPAM). HPAM accumulates and transforms continuously in the environment, producing a large amount of toxic and harmful polymer-containing wastewater and polymer-containing sludge. Therefore, it is very necessary to remove partially hydrolyzed polyacrylamide from organic wastewater. However, the treatment of oily wastewater containing partially hydrolyzed polyacrylamide is more difficult than that of ordinary oily wastewater. Existing treatment methods generally require multi-step treatment to achieve the treatment standards for oily wastewater containing partially hydrolyzed polyacrylamide. How to efficiently remove partially hydrolyzed polyacrylamide while achieving oil-water separation in one step has always been a difficult problem in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0003] Amphiphilic solid particle emulsifiers have excellent emulsification ability, achieve emulsification by reducing the interfacial tension between the two phases, have high interfacial desorption energy, and achieve efficient and stable emulsification of the emulsion. If the amphiphilic solid particles are magnetic, the emulsified droplets are magnetic, and the dispersed phase droplets can be manipulated. Based on this, the use of magnetic amphiphilic solid particles can achieve the treatment of oily wastewater, achieve the emulsification of the oil phase in water, thereby achieving the stability of the dispersed phase oil droplets, and achieve the migration and enrichment of the oil droplets under the control of the external magnetic field, thereby achieving oil-water separation. However, although the existing amphiphilic solid particle emulsifier can successfully achieve oil-water separation when used to treat partially hydrolyzed polyacrylamide oily wastewater, it cannot efficiently remove partially hydrolyzed polyacrylamide in one step. Therefore, it is very meaningful to develop an amphiphilic solid particle emulsifier that can efficiently remove partially hydrolyzed polyacrylamide in oily wastewater. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetic multi-functional organic-inorganic composite amphiphilic particle and a preparation method thereof, so as to solve the technical problem in the prior art that oily wastewater containing partially hydrolyzed polyacrylamide is difficult to be treated in one step to meet the standards.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In the first aspect, the present invention provides a magnetic multi-functional organic-inorganic composite amphiphilic particle, which comprises a core-shell separated magnetic Fe3O4 particle core and a silica shell layer; the outer surface of the silica shell layer comprises a hydrophilic part and a hydrophobic part, the hydrophilic part is modified by an amino-containing silane coupling agent on the outer surface of the silica shell layer so that the outer surface of the silica shell layer has amino groups, and the amino groups are grafted with polydopamine; polydiethylaminoethyl methacrylate (PDEAEMA) is grafted on the inner surface of the silica shell layer and the surface of the magnetic Fe3O4 particle core, and the silica shell layer has a microporous structure.

[0007] It should be noted that the "micropore structure" mentioned in the present invention includes the intermolecular voids existing in the silica macromolecular skeleton and the defects generated during the core-shell separation of the silica shell from the magnetic Fe3O4 particle core, and even micropores and capillaries with a pore size of 0.5 to 50 nm.

[0008] The magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention are coated with a layer of silicon dioxide shell on the outside of the magnetic Fe3O4 particle core, which can protect the internal magnetic Fe3O4 particle core and resist corrosion of the internal magnetic Fe3O4 particle core by hydrochloric acid, sulfuric acid, nitric acid, etc. within a certain period of time, thereby ensuring the industrial application of the magnetic multi-functional organic-inorganic composite amphiphilic particles.

[0009] The outer surface of the silica shell layer of the magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention includes both a hydrophilic part and a hydrophobic part, so that the magnetic multi-functional organic-inorganic composite amphiphilic particles have amphiphilicity. Compared with traditional homogeneous particles, they have more stable emulsification properties and can emulsify oil and water phases more stably and more widely to form a stable oil-in-water emulsion, providing a stability basis for the manipulation of emulsion droplets.

[0010] Furthermore, the functional groups on the outer surface of the silica shell of the magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention have electrostatic and other interactions with the partially hydrolyzed polyacrylamide, which promotes the adsorption of the partially hydrolyzed polyacrylamide on the outer surface of the silica shell; and the polydopamine grafted on the amino group of the hydrophilic part further increases the adhesion of the amphiphilic particles to the partially hydrolyzed polyacrylamide, thereby improving the effect of the amphiphilic particles in removing partially hydrolyzed polyacrylamide from sewage. At the same time, after achieving the adsorption and adhesion of the partially hydrolyzed polyacrylamide, the internal structural composition of the amphiphilic particles wets the partially hydrolyzed polyacrylamide adsorbed and adhered to the outer surface of the silica shell, which promotes the adsorption process of the partially hydrolyzed polyacrylamide into the silica shell. The PDEAEMA grafted on the inner surface of the silica shell and the surface of the core of the magnetic Fe3O4 particles forms a brush-like coating, which increases the specific surface area and enhances the hydrogen bond density. The microporous structure on the silica shell provides a channel for the migration and transmission of partially hydrolyzed polyacrylamide. The weak acidity of partially hydrolyzed polyacrylamide itself is conducive to the transfer adsorption of partially hydrolyzed polyacrylamide from the outer surface of the silica shell to the PDEAEMA inside the shell. Thereby, the adsorption and migration capture of partially hydrolyzed polyacrylamide by PDEAEMA is realized. The magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention greatly improve the adsorption capacity and efficiency of partially hydrolyzed polyacrylamide through the combination of internal and external structures.

[0011] The magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention can be recycled and reused. The recycling method can use a benign solvent (such as ethanol) of partially hydrolyzed polyacrylamide to wash and extract the used magnetic multi-functional organic-inorganic composite amphiphilic particles, so that the adsorbed partially hydrolyzed polyacrylamide is removed, thereby realizing the reuse of the magnetic multi-functional organic-inorganic composite amphiphilic particles. It is also possible to utilize the pH-sensitive characteristic of PDEAEMA. PDEAEMA shows hydrophilic properties at relatively low pH values ​​and hydrophobic properties at relatively high pH values. This characteristic can be used to achieve repeated adsorption and desorption of partially hydrolyzed polyacrylamide by PDEAEMA, so that the magnetic multi-functional organic-inorganic composite amphiphilic particles can be reused, greatly reducing the material cost of sewage treatment.

[0012] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0013] The hydrophilic part of the outer surface of the silica shell is modified with 3-aminopropyltriethoxysilane to have amino groups, which can produce weak interactions with partially hydrolyzed polyacrylamide with carboxyl groups, thereby achieving adsorption of partially hydrolyzed polyacrylamide.

[0014] According to some embodiments of the present invention, the hydrophobic portion is obtained by modifying the outer surface of the silica shell layer with an alkyl-containing silane coupling agent.

[0015] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0016] According to some embodiments of the present invention, the area of ​​the hydrophilic portion accounts for 1 / 3 to 2 / 3 of the total surface area of ​​the magnetic multi-functional organic-inorganic composite amphiphilic particles.

[0017] According to some embodiments of the present invention, the particle size of the magnetic multi-functional organic-inorganic composite amphiphilic particles is 100 nm<r≤1000 nm.

[0018] In a second aspect, the present invention provides a method for preparing magnetic multi-functional organic-inorganic composite amphiphilic particles, comprising:

[0019] S1. Dispersing magnetic Fe3O4 particles and tetraethyl orthosilicate in an alcohol solvent to obtain silicon-coated iron magnetic particles;

[0020] S2. The silicon-coated iron magnetic particles are dispersed in water, paraffin is added, heated until the paraffin is completely melted, stirred and mixed, cooled and filtered to obtain paraffin balls formed by the silicon-coated iron magnetic particles embedded in the surface of the paraffin;

[0021] S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles;

[0022] S4. The hydrophilic modified particles are dispersed in an alcohol solvent, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles;

[0023] S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles;

[0024] S6. The amphiphilic modified particles separated from the core-shell are dispersed in an alcohol solvent, 4-(chloromethyl)phenyltrimethoxysilane is added for modification reaction; and then grafted with diethylaminoethyl methacrylate (DEAEMA) to obtain grafted polydiethylaminoethyl methacrylate particles;

[0025] S7. The particles grafted with poly(diethylaminoethyl methacrylate) are dispersed in a solvent, dopamine is added, and the mixture is stirred for reaction. After the reaction is completed, the magnetic multi-functional organic-inorganic composite amphiphilic particles are obtained.

[0026] The preparation method of the magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention includes the processes of silica shell coating, hydrophilic modification, hydrophobic modification, acid etching, 4-(chloromethyl)phenyltrimethoxysilane modification, grafting of polydiethylaminoethyl methacrylate (PDEAEMA) and grafting of polydopamine. Specifically, magnetic Fe3O4 particles are used as carriers, and ethyl orthosilicate is used to hydrolyze the surface of magnetic Fe3O4 particles, and the magnetic Fe3O4 particles are coated by a sol-gel process to form a silicon-coated iron core-shell structure. Paraffin is then used as the oil phase, and silicon-coated iron magnetic particles are used as solid particle emulsifiers. When the temperature is higher than the paraffin phase transition temperature, the oil-water phase is emulsified to form a stable water-coated paraffin emulsion. After the emulsion is cooled, the paraffin phase solidifies and is separated from the water phase to obtain paraffin balls formed by silicon-coated iron magnetic particles embedded in the paraffin surface, and the silicon-coated iron magnetic particles are partially embedded in the paraffin and partially exposed outside the paraffin. Then, the outer surface of the silicon-coated iron magnetic particles exposed outside the paraffin is modified to be hydrophilic; then the paraffin is removed to expose the part of the silicon-coated iron magnetic particles that was previously protected by the paraffin, and the outer surface of this part is modified to be hydrophobic, so as to obtain amphiphilic particles whose particle surface includes both hydrophilic and hydrophobic parts. Then, an acid etching treatment is performed to reduce the size of the magnetic Fe3O4 particles, separate them from the silica shell layer, and generate a hollow structure between the core-shell structure. Further, 4-(chloromethyl)phenyltrimethoxysilane is used to modify the surface of the magnetic Fe3O4 particles and the inner surface of the silica shell layer with benzyl chloride [4-(chloromethyl)phenyl]. Benzyl chloride has high activity and can be grafted with polydiethylaminoethyl methacrylate (PDEAEMA) through ATRP (atom transfer radical polymerization) reaction. Finally, the particles are reacted with dopamine to graft polydopamine. The magnetic multi-functional organic-inorganic composite amphiphilic particles are obtained.

[0027] In the present invention, in view of the characteristic that magnetic Fe3O4 particles are not resistant to acidic solutions, tetraethyl orthosilicate is used to realize hydrolysis on the surface of magnetic Fe3O4 particles, and a relatively dense silica shell structure is formed on the surface of magnetic Fe3O4 particles through a sol-gel process, so that the magnetic Fe3O4 particles inside thereof are protected, and the corrosion of the magnetic Fe3O4 particle core by hydrochloric acid, sulfuric acid, nitric acid, etc. can be resisted within a certain period of time, which provides an important guarantee for the industrial application of magnetic particles. In addition, the silica shell in the present invention is a polymer formed by the hydrolysis and condensation of tetraethyl orthosilicate, and is a macromolecular skeleton composed of silicon oxygen bonds. Although the silica shell is relatively dense, in the sol-gel process of tetraethyl orthosilicate hydrolysis, the SiO2 macromolecular skeleton formed by the condensation reaction still has intermolecular gaps, which ensures the smooth progress of the subsequent acid etching treatment, 4-(chloromethyl)phenyltrimethoxysilane modification and grafting PDEAEMA process.

[0028] In the present invention, after acid etching, the magnetic Fe3O4 particles are reduced and core-shell separation occurs. This process will further cause defects in the silica shell, even micropores or capillaries. The micropore structure composed of the intermolecular gaps in the silica shell provides a channel for the transmission and migration of partially hydrolyzed polyacrylamide to the inside of the silica shell. The acid etching reagent uses acetic acid, which can make the etching slow, ensure that the etching process is controllable, and make the surface of the core of the magnetic Fe3O4 particles smoother; if hydrochloric acid, sulfuric acid, etc. are used, it is difficult to control the etching process, which can easily lead to excessive etching, thereby making the magnetic properties of the particles too weak or even completely disappear.

[0029] According to some embodiments of the present invention, the alcohol solvent includes at least one of methanol, ethanol, propanol, butanol, isopropanol, and cyclohexanol.

[0030] According to some embodiments of the present invention, the stirring and mixing speed in step S2 is 1000-5000 rpm.

[0031] In the present invention, the stirring speed in step S2 will directly affect the emulsification process of the particulate emulsifier (silicon-coated iron magnetic particles), and directly lead to the stabilization of the emulsion interface by the particulate emulsifier. When the stirring speed is less than 1000rpm, the stirring speed is too low, the particulate emulsifier is difficult to deliver to the interface, the interface cannot be stabilized, and the emulsion is easy to break; when the stirring speed is greater than 5000rpm, the stirring speed is too high, and the particulate emulsifier is forced to pull at the interface, which easily leads to interface instability and emulsion breaking. Therefore, in order to ensure emulsification and interface stability, it is advisable that the stirring speed in step S2 is controlled at 1000-5000rpm.

[0032] According to some embodiments of the present invention, the stirring and mixing time in step S2 is 3 to 5 minutes.

[0033] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0034] The outer surface of the silicon-coated iron magnetic particles is locally hydrophilically modified by 3-aminopropyltriethoxysilane in dimethyl sulfoxide. The sol-gel composite is achieved on the outer surface of the silicon-coated iron magnetic particles exposed outside the paraffin wax through a hydrolysis process. Amino groups are modified on one side of the outer surface of the silicon-coated iron magnetic particles to achieve adsorption of partially hydrolyzed polyacrylamide.

[0035] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0036] The local hydrophobic modification of the outer surface of silicon-coated iron magnetic particles by using n-octyltriethoxysilane is firstly carried out by removing paraffin with an alcohol solvent, so that the protected part of the silicon-coated iron magnetic particles embedded in the paraffin is exposed, and then the part of the silicon-coated iron magnetic particles exposed from the embedded paraffin is hydrolyzed by n-octyltriethoxysilane to achieve surface sol-gel composite, and the other side of the outer surface of the silicon-coated iron magnetic particles is modified with n-octyl.

[0037] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to tetraethyl orthosilicate is 1:(0.1-1).

[0038] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the paraffin is 1:(10-200).

[0039] According to some embodiments of the present invention, the mass ratio of paraffin to water is 1:(2-10).

[0040] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01).

[0041] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01).

[0042] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01).

[0043] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the diethylaminoethyl methacrylate is 1:(0.02-0.1).

[0044] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the dopamine is 1:(0.001-0.01).

[0045] According to some embodiments of the present invention, the particle size of the magnetic Fe3O4 particles is 100-500 nm.

[0046] According to some embodiments of the present invention, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

[0047] In the present invention, if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is less than 100:99, it means that the gap between the silica shell and the magnetic Fe3O4 particle core is too small, which will affect the adsorption capacity of the magnetic multi-functional organic-inorganic composite amphiphilic particles to partially hydrolyzed polyacrylamide; if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is greater than 100:10, it means that the size of the magnetic Fe3O4 particle core is too small, which will lead to serious magnetic attenuation and difficulty in achieving magnetic manipulation of the external magnetic field.

[0048] According to some embodiments of the present invention, the grafting reaction includes: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction in a nitrogen atmosphere at 60-100°C.

[0049] According to some embodiments of the present invention, the solvent used in the grafting reaction includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0050] According to some embodiments of the present invention, the solvent used to disperse the particles grafted with polydiethylaminoethyl methacrylate includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0051] According to some embodiments of the present invention, in step S1, the magnetic Fe3O4 particles and tetraethyl orthosilicate are dispersed in an alcohol solvent by ultrasound and stirring for 12 to 24 hours. Preferably, the ultrasound frequency is 60 to 80 Hz and / or the stirring speed is 50 to 100 rpm.

[0052] According to some embodiments of the present invention, in step S2, the silicon-coated iron magnetic particles are dispersed in water by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0053] According to some embodiments of the present invention, in step S3, the paraffin balls are dispersed in dimethyl sulfoxide by stirring, and preferably, the stirring speed is 50 to 100 rpm;

[0054] According to some embodiments of the present invention, the stirring reaction time in step S3 is 5 to 6 hours.

[0055] According to some embodiments of the present invention, in step S4, the hydrophilic modified particles are dispersed in the alcohol solvent by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 200-300 rpm.

[0056] According to some embodiments of the present invention, the stirring reaction time in step S4 is 5 to 6 hours.

[0057] According to some embodiments of the present invention, mixing the amphiphilic modified particles with acetic acid for 8-12 hours in step S5 comprises: dispersing the amphiphilic modified particles in water, adding acetic acid, and mixing for 8-12 hours by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0058] According to some embodiments of the present invention, the stirring reaction time in step S7 is 5 to 6 hours.

[0059] In a third aspect, the present invention provides a magnetic multi-functional organic-inorganic composite amphiphilic particle prepared by the preparation method described in the second aspect.

[0060] In a fourth aspect, the present invention provides the use of the magnetic multi-functional organic-inorganic composite amphiphilic particles described in the first aspect or the magnetic multi-functional organic-inorganic composite amphiphilic particles described in the third aspect in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0061] The beneficial effects of the present invention are at least:

[0062] (1) The magnetic multifunctional organic-inorganic composite amphiphilic particles provided by the present invention have excellent emulsification properties. The droplets stabilized by the emulsification using the magnetic multifunctional organic-inorganic composite amphiphilic particles can be manipulated by an external magnetic field to achieve the enrichment and migration of oil droplets, thereby achieving oil-water separation.

[0063] (2) The magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention have a core-shell separation structure, and the poly(diethylaminoethyl methacrylate) grafted in the cavity between the core and the shell has a good adsorption effect on partially hydrolyzed polyacrylamide, and the amino groups on the surface of the particles and the polydopamine grafted on the amino groups also have adsorption properties, which can further improve the adsorption effect on partially hydrolyzed polyacrylamide, thereby realizing one-step efficient treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0064] (3) The magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention can be reused multiple times, and the adsorption capacity for partially hydrolyzed polyacrylamide will not decrease significantly, which can greatly reduce the material cost of sewage treatment.

[0065] (4) The preparation method of the magnetic multi-functional organic-inorganic composite amphiphilic particles provided by the present invention has a simple process, low cost and readily available raw materials, and can achieve industrial mass production at the ton level. DETAILED DESCRIPTION

[0066] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0067] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0068] Example 1

[0069] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1.0 g of tetraethyl orthosilicate, and add 60 Hz ultrasound and 100 rpm overhead stirring. Maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles for 12 hours to separate silicon-encapsulated iron magnetic particles.

[0070] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 20g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface.

[0071] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@SiO2-NH2 particles with amino groups modified on one side of the surface.

[0072] S4. Disperse Fe3O4@SiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 60 Hz ultrasound. Add 20 mg of n-octyltriethoxysilane to the dispersion, continue stirring for 6 h, and separate the solid particles using an external magnetic field to obtain C8-Fe3O4@SiO2-NH2 particles.

[0073] S5. The C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while ultrasound was applied at 60 Hz to obtain core-shell separated C8-Fe3O4@SiO2-NH2 particles;

[0074] S6. The core-shell separated C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of ethanol, 10 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain modified C8-Fe3O4@SiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2-NH2 particles were added, and 0.1 g of DEAEMA was added, and N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h to obtain particles grafted with polydiethylaminoethyl methacrylate;

[0075] S7. The particles grafted with poly(diethylaminoethyl methacrylate) were dispersed in a solvent, 20 mg of dopamine was added, and the mixture was stirred for 6 h. After the reaction, magnetic multi-functional organic-inorganic composite amphiphilic particles were obtained.

[0076] Example 2

[0077] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 0.3 g of tetraethyl orthosilicate, add 80 Hz ultrasound and 80 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 24 hours, and separate silicon-encapsulated iron magnetic particles.

[0078] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 80Hz ultrasound and 80rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 50g of paraffin wax (phase transition temperature is 52°C), and continue stirring until the paraffin wax is completely melted. Turn off the ultrasound and increase the stirring speed to 1000rpm, and continue stirring for 5min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface.

[0079] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 80 rpm. Add 3 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 5 h. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@SiO2-NH2 particles with amino groups modified on one side of the surface.

[0080] S4. Disperse Fe3O4@SiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 80 Hz ultrasound. Add 3 mg of n-octyltriethoxysilane to the dispersion, continue stirring for 5 h, and separate the solid particles using an external magnetic field to obtain C8-Fe3O4@SiO2-NH2 particles.

[0081] S5. The C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 8 h using an overhead stirrer at a speed of 80 rpm, while 80 Hz ultrasound was applied to obtain core-shell separated C8-Fe3O4@SiO2-NH2 particles;

[0082] S6. The core-shell separated C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of ethanol, 3 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 80 rpm for 12 h to obtain modified C8-Fe3O4@SiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2-NH2 particles were added, and 0.04 g of DEAEMA was added, and N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 80 rpm for 3 h to obtain particles grafted with diethylaminoethyl polymethacrylate;

[0083] S7. The particles grafted with poly(diethylaminoethyl methacrylate) were dispersed in a solvent, 3 mg of dopamine was added, and the reaction was stirred for 6 hours. After the reaction was completed, magnetic multi-functional organic-inorganic composite amphiphilic particles were obtained.

[0084] Example 3

[0085] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 2.0 g of tetraethyl orthosilicate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate silicon-encapsulated iron magnetic particles.

[0086] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 20g of paraffin wax (phase transition temperature is 52°C), and continue stirring until the paraffin wax is completely melted. Turn off the ultrasound and increase the stirring speed to 5000rpm, and continue stirring for 4min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface.

[0087] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 60 rpm. Add 10 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@SiO2-NH2 particles with amino groups modified on one side of the surface.

[0088] S4. Disperse Fe3O4@SiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 200 rpm, and apply 80 Hz ultrasound. Add 10 mg of n-octyltriethoxysilane to the dispersion, continue stirring for 6 h, and separate the solid particles using an external magnetic field to obtain C8-Fe3O4@SiO2-NH2 particles.

[0089] S5. The C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 12 h using an overhead stirrer at a speed of 60 rpm, while 80 Hz ultrasound was applied to obtain core-shell separated C8-Fe3O4@SiO2-NH2 particles;

[0090] S6. The core-shell separated C8-Fe3O4@SiO2-NH2 particles were dispersed in 100 mL of ethanol, 15 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 60 rpm for 12 h to obtain modified C8-Fe3O4@SiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2-NH2 particles were added, and 0.2 g of DEAEMA was added, and N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 60 rpm for 3 h to obtain particles grafted with diethylaminoethyl polymethacrylate;

[0091] S7. The particles grafted with poly(diethylaminoethyl methacrylate) were dispersed in a solvent, 10 mg of dopamine was added, and the mixture was stirred for 6 h. After the reaction, magnetic multi-functional organic-inorganic composite amphiphilic particles were obtained.

[0092] Example 4

[0093] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1.0 g of tetraethyl orthosilicate, and add 60 Hz ultrasound and 100 rpm overhead stirring. Maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles for 12 hours to separate silicon-encapsulated iron magnetic particles.

[0094] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 20g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 500rpm. Because the stirring speed is too low, the particles cannot be delivered to the oil-water interface by mechanical force, the silicon-coated iron magnetic particles cannot be stabilized at the oil-water interface, the oil-water two phases cannot be stably emulsified, the water phase and the oil phase are still two phases, and the paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface cannot be obtained.

[0095] Example 5

[0096] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1.0 g of tetraethyl orthosilicate, and add 60 Hz ultrasound and 100 rpm overhead stirring. Maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles for 12 hours to separate silicon-encapsulated iron magnetic particles.

[0097] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 20g of paraffin wax (phase transition temperature is 52°C), and continue stirring until the paraffin wax is completely melted. Turn off the ultrasound and increase the stirring speed to 6000rpm. Due to the high stirring speed, although the silicon-coated iron magnetic particles are mechanically delivered to the oil-water interface for emulsification, the excessively fast mechanical stirring causes the particles to peel off at the interface, making the interface unstable and causing demulsification, and it is impossible to obtain the paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface.

[0098] Comparative Example 1

[0099] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1.0 g of tetraethyl orthosilicate, and add 60 Hz ultrasound and 100 rpm overhead stirring. Maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles for 12 hours to separate silicon-encapsulated iron magnetic particles.

[0100] S2. Disperse the silicon-coated iron magnetic particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the silicon-coated iron magnetic particles. Raise the water temperature to 80°C, add 20g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the silicon-coated iron magnetic particles embedded in the paraffin surface.

[0101] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@SiO2-NH2 particles with amino groups modified on one side of the surface.

[0102] S4. Disperse Fe3O4@SiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 60 Hz ultrasound. Add 20 mg of n-octyltriethoxysilane to the dispersion, continue stirring for 6 h, and separate the solid particles using an external magnetic field to obtain C8-Fe3O4@SiO2-NH2 particles;

[0103] S5. Disperse the C8-Fe3O4@SiO2-NH2 particles in a solvent, add 20 mg of dopamine, stir and react for 6 hours to obtain particles.

[0104] Comparative Example 2

[0105] S1. Disperse 2.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1.0 g of tetraethyl orthosilicate, and add 60 Hz ultrasound and 100 rpm overhead stirring. Maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles for 12 hours to separate silicon-encapsulated iron magnetic particles.

[0106] S2. The silicon-coated iron magnetic particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while adding 60 Hz ultrasound to obtain core-shell separated silicon-coated iron magnetic particles;

[0107] S3. The core-shell separated silicon-coated ferromagnetic particles were dispersed in 100 mL of ethanol, 10 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain modified silicon-coated ferromagnetic particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the above-mentioned modified silicon-coated ferromagnetic particles were added, and 0.1 g of DEAEMA was added, and N2 was introduced for deoxygenation for 30 min. The temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h. After the reaction, the particles were obtained.

[0108] Comparative Example 3

[0109] The particles were prepared by referring to the preparation method of Example 1, except that the acetic acid was replaced by an equal volume of dilute hydrochloric acid (pH 6).

[0110] Comparative Example 4

[0111] The particles were prepared by referring to the preparation method of Example 1, except that acetic acid was replaced by an equal volume of sulfuric acid.

[0112] Performance Evaluation

[0113] (I) The particle size of the particles of each embodiment and comparative example was measured using a scanning electron microscope, and the results are shown in the following table:

[0114] Group Particle size (nm) Example 1 260 Example 2 212 Example 3 260 Comparative Example 1 260 Comparative Example 2 220 Comparative Example 3 260 Comparative Example 4 260

[0115] (II) Wastewater treatment effect

[0116] 1 kg of the particles prepared in each embodiment and comparative example were added to 10 t of partially hydrolyzed polyacrylamide oily wastewater (COD value was 2020, petroleum pollutant content was 52.3 mg / L, and partially hydrolyzed polyacrylamide content was 103.05 mg / L), and the oily wastewater was emulsified by stirring at a speed of 1000 rpm for 1 min using a shearing machine; then the migration and enrichment of the emulsified oil droplets of the magnetic particles were achieved by controlling the external magnetic field. The treated wastewater was tested, and the test method is shown in the following table:

[0117]

[0118] The test results are shown in the following table:

[0119]

[0120] (III) Cyclic performance

[0121] The magnetic multi-functional organic-inorganic composite amphiphilic particles are washed and regenerated by a solvent method, thereby realizing the recycling of the magnetic multi-functional organic-inorganic composite amphiphilic particles. The specific treatment method includes: collecting the magnetic multi-functional organic-inorganic composite amphiphilic particles prepared in Example 1 after wastewater treatment, washing with ethanol, the mass ratio of ethanol to amphiphilic particles is 10:1, and then freeze-drying after washing to obtain regenerated particles.

[0122] The regenerated particles were used to repeat the treatment process of partially hydrolyzed polyacrylamide-containing oily wastewater in step (ii), and the indicators of the treated wastewater were similar to the treatment effect of the first wastewater treatment using the magnetic multi-functional organic-inorganic composite amphiphilic particles in Example 1. The magnetic multi-functional organic-inorganic composite amphiphilic particles can be recycled for more than 100 times, and the removal effect of COD, petroleum and partially hydrolyzed polyacrylamide will not be significantly deteriorated.

[0123] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A magnetic multi-functional organic-inorganic composite amphiphilic particle, characterized in that: The invention comprises a core-shell separated magnetic Fe3O4 particle inner core and a silica shell layer; the outer surface of the silica shell layer comprises a hydrophilic part and a hydrophobic part, the hydrophilic part is modified by an amino-containing silane coupling agent on the outer surface of the silica shell layer so that the outer surface of the silica shell layer carries amino groups, and the amino groups are grafted with polydopamine; polydiethylaminoethyl methacrylate is grafted on the inner surface of the silica shell layer and the surface of the magnetic Fe3O4 particle inner core, and the silica shell layer has a microporous structure.

2. The magnetic multi-functional organic-inorganic composite amphiphilic particles according to claim 1, characterized in that: The amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the hydrophobic part is obtained by modifying the outer surface of the silica shell layer with an alkyl-containing silane coupling agent; preferably, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane; And / or, the particle size of the magnetic multi-functional organic-inorganic composite amphiphilic particles is 100nm<r≤1000nm.

3. A method for preparing magnetic multi-functional organic-inorganic composite amphiphilic particles, characterized in that: include: S1. Dispersing magnetic Fe3O4 particles and tetraethyl orthosilicate in an alcohol solvent to obtain silicon-coated iron magnetic particles; S2. The silicon-coated iron magnetic particles are dispersed in water, paraffin is added, heated until the paraffin is completely melted, stirred and mixed, cooled and filtered to obtain paraffin balls formed by the silicon-coated iron magnetic particles embedded in the surface of the paraffin; S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles; S4. The hydrophilic modified particles are dispersed in an alcohol solvent, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles; S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles; S6. The amphiphilic modified particles separated from the core-shell are dispersed in an alcohol solvent, 4-(chloromethyl)phenyltrimethoxysilane is added for modification reaction; and then grafted with diethylaminoethyl methacrylate to obtain grafted polydiethylaminoethyl methacrylate particles; S7. The particles grafted with poly(diethylaminoethyl methacrylate) are dispersed in a solvent, dopamine is added, and the mixture is stirred for reaction. After the reaction is completed, the magnetic multi-functional organic-inorganic composite amphiphilic particles are obtained.

4. The preparation method according to claim 3, characterized in that: The stirring and mixing speed in step S2 is 1000-5000 rpm. Preferably, the stirring and mixing time in step S2 is 3-5 min.

5. The preparation method according to claim 3 or 4, characterized in that: The amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The mass ratio of the magnetic Fe3O4 particles to tetraethyl orthosilicate is 1:(0.1-1); and / or, the mass ratio of the magnetic Fe3O4 particles to the paraffin is 1:(10-200); And / or, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to the 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to the diethylaminoethyl methacrylate is 1:(0.02-0.1); And / or, the mass ratio of the magnetic Fe3O4 particles to the dopamine is 1:(0.001-0.01).

7. The preparation method according to any one of claims 3 to 6, characterized in that: The particle size of the magnetic Fe3O4 particles is 100 to 500 nm; And / or, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

8. The preparation method according to any one of claims 3 to 7, characterized in that: The grafting reaction comprises: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction under a nitrogen atmosphere at 60-100° C.

9. A magnetic multi-functional organic-inorganic composite amphiphilic particle prepared by the preparation method according to any one of claims 3 to 8.

10. Use of the magnetic multifunctional organic-inorganic composite amphiphilic particles according to claim 1 or 2 or the magnetic multifunctional organic-inorganic composite amphiphilic particles according to claim 9 in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

Citation Information

Patent Citations

  • Preparation method of amphiphilic Janus hierarchical pore microcapsule with opening structure

    CN106732221A

  • Polymer mixed grafted and modified magnetic nano silicon dioxide and application thereof

    CN107417922A

  • Cellulose microsphere adsorbent, preparation method thereof and hemoperfutor

    CN112191232A

  • Magnetic snowman-shaped asymmetric Janus particle and preparation method thereof

    CN114736322A

  • Functional particles and water treatment method employing the same

    US20090321363A1

Cited By

  • Residual polyacrylamide flocculating agent settling agent in sand-making circulating water as well as preparation method and application thereof

    CN121470644A